Nursing Care for Hyperthermia in An.A with Febrile Seizures and Application of Tepid Water Sponge in the Small Subi Ward of Dr. Midiyato Suratani Hospital, Tanjungpinang: A Case Study In Pediactic Nursing Care - Astrid Astrid (Jurnal Ilmiah Cerebral Medika, 2026)
Febrile seizures are a common neurological disorder in children aged 6 months to 5 years and are often triggered by hyperthermia. Appropriate treatment is crucial to prevent complications such as brain damage and impaired growth and development. One effective non-pharmacological method for lowering a child's body temperature is tepid water sponging (TWS), a warm compress technique performed by wiping the child's body in the body's creases to stimulate vasodilation and accelerate heat loss. This study aimed to evaluate the implementation of TWS as part of hyperthermia nursing care for children with febrile seizures in the Subi Kecil Ward of Dr. Midiyato Suratani Navy Hospital, Tanjungpinang. The method used was a case study with a nursing care approach for one pediatric patient (An. A) experiencing febrile seizures. The nursing process included assessment, diagnosis, intervention, implementation, and evaluation. The results showed that TWS was effective in lowering the patient's body temperature from 39.2°C to 37.0°C in less than an hour. Furthermore, the child's general condition improved, as evidenced by decreased irritability, increased appetite, and the absence of recurrent seizures. In conclusion, TWS is a safe, inexpensive, and effective intervention for reducing hyperthermia in children with febrile seizures. This technique can be used as an alternative non-pharmacological nursing intervention in treating hyperthermia, particularly in children in healthcare facilities.